2008
DOI: 10.1007/s00535-008-2264-8
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of non-B non-C hepatocellular carcinoma in the eastern district of Tokyo

Abstract: Alcohol consumption and NAFLD may be important etiological factors in non-B non-C HCC. Periodic medical assessments for all patients with non-B non-C cirrhosis are crucial for early diagnosis and curative therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 35 publications
(34 reference statements)
2
46
2
Order By: Relevance
“…The analysis of the characteristics of NBNC HCC indicated that the mean age, rate of complications associated with diabetes and BMI were significantly higher in these cases compared with cases of virus-related HCC, in agreement with previous reports (5)(6)(7)(8)(9)(10)(11)(12). Patients with NBNC HCC exhibited a good liver function, although a number of patients presented with a large tumor size (6), possibly as they were not examined periodically due to the absence of hepatitis virus infection.…”
Section: Discussionsupporting
confidence: 91%
“…The analysis of the characteristics of NBNC HCC indicated that the mean age, rate of complications associated with diabetes and BMI were significantly higher in these cases compared with cases of virus-related HCC, in agreement with previous reports (5)(6)(7)(8)(9)(10)(11)(12). Patients with NBNC HCC exhibited a good liver function, although a number of patients presented with a large tumor size (6), possibly as they were not examined periodically due to the absence of hepatitis virus infection.…”
Section: Discussionsupporting
confidence: 91%
“…Occult infection with HBV represented by the presence of antibody to hepatitis B core antigen (anti-HBc) has been considered as a risk factor of non-B, non-C HCC defined as negative for both HBsAg and anti-HCV antibody [27,28]. Indeed the prevalence of anti-HBc antibody was higher in this study compared to a previous report in blood donors [29].…”
Section: Discussioncontrasting
confidence: 50%
“…40 On the Eastern side, a study from Japan found that 17 of 320 (5.3%) HCC cases were either associated with NASH or had a cryptogenic etiology. 41 Cryptogenic hepatocellular carcinoma accounted for 5.4% of all HCC in Korea, and this group had higher BMI, TG levels, DM, and HTN compared with HCC with well-defined etiologies. 42 In another study from Korea, 20 of 36 (56%) patients with CHCC had at least two risk factors for NAFLD.…”
Section: Non-alcoholic Fatty Liver Disease and Cryptogenic Hepatocellmentioning
confidence: 90%
“…Also, the prevalence of obesity and diabetes was significantly higher in this cohort. 41 Formation of HCC in noncirrhotic livers in NASH is a cause of concern, and appropriate screening protocols for HCC in NASH need to be formulated like those for hepatitis B infection.…”
Section: Overweight/obesitymentioning
confidence: 99%